Pruning methods to MLP neural networks considering proportional apparent error rate for classification problems with unbalanced data - Silvestre, Miriam Rodrigues [UNESP]; Ling, Lee Luan (Elsevier B.V., 2014)
This article deals with classification problems involving unequal probabilities in each class and discusses metrics to systems that use multilayer perceptrons neural networks (MLP) for the task of classifying new patterns. In addition we propose three new pruning methods that were compared to other seven existing methods in the literature for MLP networks. All pruning algorithms presented in this paper have been modified by the authors to do pruning of neurons, in order to produce fully connected MLP networks but being small in its intermediary layer. Experiments were carried out involving the E. coli unbalanced classification problem and ten pruning methods. The proposed methods had obtained good results, actually, better results than another pruning methods previously defined at the MLP neural network area. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Unbalanced data; Pruning method; MLP neural network; Proportional apparent error rate